PELATIHAN PENGGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN KEMAMPUAN PEDAGOGIK GURU - Wulanda, Mastarita Nova; Agnesa, Tia; Muslimahayati, Muslimahayati (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Learning loss due to the Covid-19 pandemic is a big homework assignment for all aspects of education. The rapid development of science and technology requires every individual to adapt themselves. Artificial Intelligence (AI) has an interesting potential to be linked to learning. The objectives of this training are a) to increase teachers' pedagogical competence in using Artificial Intelligence (AI)-based technology to create learning tools in schools; and b) Create innovative and effective learning tools and meaningful learning experiences for students based on Artificial Intelligence (AI) in Mathematics and Science subjects at school. The method used in this community service activity is Service Learning or SL which involves direct experience, academic learning and community involvement. The community service activities are carried out through six stages of activities, namely: (1) preparation of activities and socialization, (2) training of AI-based learning making, (3) on job training and asynchronous sharing, (4) accompanying the creation of learning tools with a combination of synchronic and assynchronized communication, (5) evaluation and control of the work of the participating teachers, and (6) reporting. The results obtained by participants experienced an increase in their pedagogical competency scores with an average N-gain (increase) value of 0.23, still in the low category.